Embryonic stem cell extracellular vesicles reverse the senescence of retinal pigment epithelial cells by the p38MAPK pathway. (February 2023) - Liu, Yurun; Gu, Simin; Su, Yaru; Wang, Shoubi; Cheng, Yaqi; Sang, Xuan; Jin, Lin; Liu, Ying; Li, Chaoyang; Liu, Weiqin; Chen, Minghao; Wang, Xiaoran; et al.
Abstract: Retinal pigment epithelial (RPE) cellular senescence is regarded as an initiator for age-related macular degeneration (AMD). We previously demonstrated that by the coculture way, embryonic stem cells (ESCs) can reverse the senescence of RPE cells, but xenograft cells can cause a plethora of adverse effects. Extracellular vesicles (EVs) derived from ESCs can act as messengers to mediate nearby cell activities and have the same potential as ESCs to reverse RPE senescence. Furthermore, ESC-EVs have achieved preliminary efficacy while treating many age-related diseases. The present study aimed to test the effect of ESC-EVs on the replicative senescence model of RPE cells as well as its mechanism. The results showed that ESC-EVs enhanced the proliferative ability and cell cycle transition of senescent RPE cells, whereas reduced the senescence-associated galactosidase (SA-β-gal) staining rate, as well as the levels of mitochondrial membrane potential (MMP) and reactive oxygen species (ROS). Moreover, classical markers of cellular senescence p21 WAF1/CIP1 (p21) and p16 INK4a (p16) were downregulated. The bioinformatic analysis and further study showed that the inhibition of the p38MAPK pathway by ESC-EVs played a pivotal role in RPE cellular senescence-reversing effect, which was ameliorated or even abolished when dehydrocorydaline were administrated simultaneously, demonstrating that ESC-EVs can effectively reverse RPE cellular senesence by inhibiting the p38MAPK pathway, thus highlights the potential of ESC-derived EVs as biomaterials for preventative and protective therapy in AMD. Graphical abstract: Image 1 Highlights: ESC-EVs can enhance the proliferative ability and cell cycle transition of senescent RPE cells. ESC-EVs reduced the rate of SA-β-gal positive cells, ROS accumulation and mitochondrial membrane potential. E-EVs effectively reverse the senescece of RPE cells by inhibiting the p38MAPK pathway.